Ilmu Komunikasi dan Ilmu Hukum: Dua Pilar Dalam Meningkatkan Kesadaran Literasi Hukum Masyarakat (Studi di Lembaga Bantuan Hukum Gerakan Pemuda Ansor Kabupaten Wajo) - Sofyang, Sofyang (Widya Komunika, 2025)
This study aims to analyze the role of Communication Science and Legal Science as two main pillars in improving public legal literacy. The research was conducted at the Legal Aid Institute of the Ansor Youth Movement (LBH GP Ansor) in Wajo Regency using an empirical legal approach. Data were collected through in-depth interviews, participatory observation, and questionnaires distributed to 15 recipients of legal aid services. The results show that an interdisciplinary approach combining Communication and Law is effective in delivering legal information. Legal messages that are conveyed in a humanistic, contextual, and participatory manner can enhance public understanding of their rights and obligations. Although 60% of respondents had attended legal outreach and 73% accessed information via social media, only 40% understood basic legal procedures. These findings indicate that access to information does not automatically equate to legal comprehension, emphasizing the need for targeted communication strategies to build sustainable legal awareness.